Storage processes in Poisson approximation scheme - Koroliuk, V.S. (Інститут математики НАН України, 2008)
Discrete storage processes, given by a sum of random variables on Markov and semi-Markov processes, are approximated by the Poisson compound processes on increasing time intervals.